Current State of Clinical Trials and Regulatory Approvals with Fibroblast Activation Protein Targeting Interventions - Mosessian, Sherly; Jensen, Jessica D; Enke, Aaron S (PET clinics, 2023)
In this article, the authors review the current state of fibroblast activation protein (FAP)-targeted interventions utilizing available data from clinicaltrials.gov. Thirty-seven records were reviewed and demonstrated interventions with imaging studies comprising the largest portion of the active studies in progress, followed by therapeutic studies using non-radioligand and radioligand therapy. The efforts are in early stages of clinical development; however the field is gaining significant momentum. Completion of existing clincial studies and entrance of new products into the clincial trial phase will shed important light on the clinical utility of these interventions and shape future clinical development efforts.